The prevalence of diabetes and thyroid related autoantibodies in Sri Lankan children with type 1 diabetes and their unaffected siblings – The utility of a new screening assay - Atapattu, Navoda; Amoroso, Marie; Powell, Michael; de Silva, D. G. Harendra; de Silva, K. Shamya H.; Furmaniak, Jadwiga; Rees Smith, Bernard; Premawardhana, Lakdasa D. (Frontiers in Endocrinology, 2023)
Abstract Background There is limited information about diabetes and thyroid related autoantibodies in children with type 1 diabetes (T1D) or their siblings in Sri Lanka. Objectives To assess in T1D children and their unaffected siblings the prevalence of autoantibodies to (1) glutamic acid decarboxylase (GADA), insulinoma associated antigen-2 (IA-2A) and zinc transporter 8 (ZnT8A) using 3 Screen ICATM (3-Screen) and individual ELISA assays; (2) insulin (IAA); and (3) thyroid peroxidase (TPOA), thyroglobulin (TgA) and the TSH receptor (TSHRA). Methods We selected - (a) consecutive T1D children, and (b) their unaffected siblings of both sexes, from the T1D Registry at Lady Ridgeway Hospital, Colombo. Results The median age (IQR) of 235 T1D children and 252 unaffected siblings was 11 (8.4,13.2) and 9 (5.4,14.9) years respectively, and the duration of T1D was 23 (7,54) months. (1) T1D children (a) 79.1% were 3-Screen positive; (b) all 3-Screen positives were individual antibody positive (GADA in 74%; IA-2A 31.1%; ZnT8A 38.7%); (c) and were younger (p=0.01 vs 3-Screen negatives); (d) multiple autoantibodies were present in 45.1%; (e) IA-2A (p=0.002) and ZnT8A (p=0.006) prevalence decreased with T1D duration. (f) TPOA and TgA prevalence was higher in T1D children compared to unaffected siblings (28%, p=0.001 and 31%, p=0.004, respectively). (2) Unaffected siblings (a) 6.3% were 3-Screen positive (p=0.001 vs T1D), and 2.4% were positive for IAA; (b) four subjects had two diabetes related autoantibodies, one of whom developed dysglycaemia during follow-up. Conclusions The 3-Screen assay, used for the first time in Sri Lankan T1D children and their siblings as a screening tool, shows a high prevalence of T1D related Abs with a high correlation with individual assays, and is also a helpful tool in screening unaffected siblings for future T1D risk. The higher prevalence of thyroid autoantibodies in T1D children is consistent with polyglandular autoimmunity.